Factors Affecting the Success of Cloud-Based ERP Implementation in Manufacturing Companies in Indonesia - Vandika, Arnes Yuli; Kalsum, Ummu; Wifasari, Septi (West Science Accounting and Finance, 2025)
This study investigates the factors influencing the success of cloud-based Enterprise Resource Planning (ERP) implementation in manufacturing companies in Indonesia. Using a quantitative approach, data were collected from 100 respondents directly involved in ERP implementation, including IT personnel, system users, and project managers. The study examines four key variables: top management support, user competence, system quality, and vendor support. Data were analyzed using SPSS version 25 through descriptive statistics, validity and reliability testing, and multiple linear regression analysis. The results show that all four variables significantly affect the success of ERP implementation, with top management support being the most dominant factor. These findings underscore the importance of strategic leadership, employee preparedness, system reliability, and vendor collaboration in ensuring the effectiveness of cloud-based ERP systems in Indonesia's manufacturing sector.